2000
DOI: 10.1093/chemse/25.3.331
|View full text |Cite
|
Sign up to set email alerts
|

Decline in Taste and Odor Discrimination Abilities with Age, and Relationship between Gustation and Olfaction

Abstract: It is important to learn about changes in both taste and odor perceptions with increasing age, because the taste of foods we encounter in our daily life is strongly affected by their smell. This study discusses the difference in qualitative taste and odor discrimination between the elderly and the young. Tastants and odorants used in this study were presented not as single stimuli but as a taste mixture (sucrose and tartaric acid) and an odor mixture (beta-phenylethyl alcohol and gamma-undecalactone). The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
68
3
15

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(96 citation statements)
references
References 22 publications
6
68
3
15
Order By: Relevance
“…The causes of this decline are not completely understood, although it has been attributed to anatomical changes in some peripheral olfactory structures, such as a decrease in the number of receptors that converge in the olfactory bulb, in mitral cells, and in central olfactory areas such as the temporal lobe, the entorhinal cortex, the hippocampus, and the amygdala (Cowell et al, 1994;Kaneda et al, 2000;Price, Davis, Morris, & White, 1991). Previous research has shown that olfactory performance depends highly on the task used to assess odor performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The causes of this decline are not completely understood, although it has been attributed to anatomical changes in some peripheral olfactory structures, such as a decrease in the number of receptors that converge in the olfactory bulb, in mitral cells, and in central olfactory areas such as the temporal lobe, the entorhinal cortex, the hippocampus, and the amygdala (Cowell et al, 1994;Kaneda et al, 2000;Price, Davis, Morris, & White, 1991). Previous research has shown that olfactory performance depends highly on the task used to assess odor performance.…”
mentioning
confidence: 99%
“…Most studies on odor identification have used a rather small set of stimuli, ranging from 2 to 16 odors (Finkel, Pedersen, & Larsson, 2001;Kaneda et al, 2000;Larsson et al, 2004;Nordin, Nyroos, Maunuksela, Niskanen, & Identification of odors of edible and nonedible stimuli as affected by age and gender…”
mentioning
confidence: 99%
“…Similarly, young outperform old adults in odor quality discrimination (Hummel et al, 1998;Kaneda et al, 2000;Schemper, Voss, & Cain, 1981). In a study by de age was negatively correlated with both odor discrimination and odor identification performance.…”
Section: Olfactory Function In Normal Agingmentioning
confidence: 94%
“…Odor thresholds increase with aging (Kaneda et al, 2000;Larsson et al, 2000;Murphy, Nordin, de Wijk, Cain, & Polich, 1994;Stevens & Cain, 1987), although a loss in odor sensitivity may not always a feature in aging. For example, Nordin, Almkvist, and Berglund (2012) demonstrated that a subgroup of older subjects without any medical, health or cognitive deficits (i.e.…”
Section: Olfactory Function In Normal Agingmentioning
confidence: 99%
“…65 yaş üzerinde kişilerin yaklaşık olarak %25'inde, 4 temel tad duyusunun (tatlı, ekşi, tuzlu, acı) bir veya birden fazlasında azalma vardır. Bunun nedeni; dil tad papillarındaki sayı ve fonksiyonel azalmadır (9). Beslenmenin özendirilme-sinde, koku ve tad almanın iletilmesinin önemi büyüktür.…”
Section: Yaşlılıkta Enerji Ve Besin öğEsi Gereksinimleriunclassified